Does access to educational institutions signify gaining quality education? - Gazta, Parul and Jadhav, Jagdish (Economic and Political Weekly)
The Annual Status of Education Report has been instrumental in understanding the education trends in rural India. The ASER 2022, published after a gap of four years, draws attention to the aftermath of the COVID-19 pandemic on the primary and middle school education. While an increase in the enrolment rate is an encouraging observation, declining foundational learning abilities is a grim development. Drawing inferences from the major findings of the report, this article suggests the need for renewed collective efforts from the state, teachers, parents, and neighbourhood community to meet the new educational challenges.- Reproduced